Welfare to Temporary Work: Implications for Labor Market Outcomes - Heinrich, Carolyn J.; Mueser, Peter R.; Troske, Kenneth R. (The Review of Economics and Statistics, 2005)
We explore the effects of temporary help employment on welfare recipients' subsequent employment and welfare dynamics. We find that any employment—in temporary help services or other sectors—yields substantial benefits compared to no employment. Although welfare recipients who go to work for temporary help service firms have lower initial wages than those with jobs in other sectors, they experience faster subsequent wage growth. Two years later, they are no less likely to be employed, their wages are close to those of other workers, and they are only slightly more likely to remain on welfare.